Implementation of total productive maintenance in healthcare: A pilot study - Rungchat Chompu-Inwai (2018)
Total productive maintenance (TPM) is a method to improve and enhance productivity. TPM permanently improves the overall effectiveness of equipment, with the active involvement of operators. This paper describes the pilot implementation and evaluation of TPM for the dental units in the Dental Hospital, Faculty of Dentistry, Chiang Mai University, Thailand. The paper aims to develop a methodology for increasing the dental unit utilization and availability, as well as decreasing unplanned equipment downtime. The methodology was developed based on the first two phases of the phased equipment management approach; improvement of existing equipment and maintaining improved equipment. Both autonomous maintenance (AM) by operators and preventive maintenance (PM) were implemented. Documents such as PM manual, procedures and forms were developed. Both quantitative and qualitative research methods were used to evaluate the performance of the implemented maintenance program. The experiences from this will be useful for other healthcare organizations that would like to implement TPM. Furthermore, through a pilot study of implementing TPM in a dental hospital, the practical aspects within and beyond basic TPM theory, difficulties in the adoption of TPM and the problems encountered during the implementation are discussed. © 2008 IEEE.